PERANCANGAN SPBKLU SEPEDA MOTOR LISTRIK DAN PEMILIHAN LOKASI PEMASANGAN DI BALI SELATAN - N. W. Sindi; D. A. S. Santiari; I. A. D. Giriantari; W. G. Ariastina; I W. Sukerayasa; I N. S. Kumara; I N. Setiawan (Jurnal SPEKTRUM, 2025)
The limited availability of fossil fuel reserves and the fact that their formation takes millions of years have driven the accelerated adoption of electric vehicles as a strategic step to reduce carbon emissions. Bali, as one of the leading regions in the clean energy transition, requires adequate infrastructure support, particularly charging stations as the main facilities for electric vehicles, whose development must take into account proper location selection and design. This study focuses on the design and location selection of battery swapping stations for electric motorcycles (SPBKLU) in South Bali, including three-dimensional designs and electrical layouts, as well as location determination using the Analytical Hierarchy Process (AHP) method by evaluating potential sites. The results of this study are one optimal location for SPBKLU installation, accompanied by a three-dimensional design suited to the site’s characteristics and the SPBKLU’s electrical layout. In the future, it is expected to serve as a study and reference for the development of electric vehicle infrastructure in Bali, accelerating public adaptation to this technology.